Localization of cerebral hypoperfusion in dogs with refractory and non-refractory epilepsy using [99mTc] ethyl cysteinate dimer and single photon emission computed tomography - HUAIJANTUG, Somkiat (J Vet Med Sci, 2020)
To evaluate the localization of functional deficit area in epileptogenic zones of the brain in seven refractory and seven non-refractory epilepsy dogs using technetium 99m labeled with ethyl cysteinate dimer and interictal single photon emission computed tomography [(99m)Tc-ECD SPECT] co-registration with Magnetic Resonance Imaging (MRI). Regions showing perfusion deficits in the SPECT images were analyzed by using the standard semiquantitative evaluation method to compare the level of cortical perfusion to the maximum number of counts within the cerebellum (max C), considered the area of reference. This study showed that SPECT imaging revealed abnormalities in several regions of the brain in both epilepsy groups. The refractory epilepsy dogs showed more frequency area of hypoperfusion in temporal lobe than non-refractory group with not statistically significance (P=0.28). The result suggests the lesion in temporal might be relevance with refractory epilepsy in canine patients.